Novel Approaches for Detection Fluorescent-Labeled by Cellvizio Lab System on Hippocampal CA1 Region - Shaimi, Asma Ulhusna; Aasim, Wan Raihana Wan; Abdullah, Hasmah; Choon, Tan Soo; Wei, Ang Chee; Ismail, Zalina (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2019)
Neurosteroids have been identified in the 1981. Dehydroepiandrosterone sulphate (DHEAS) is one of the vital neurosteroids that de novo synthesized in the nervous system from cholesterol precursor (Baulieu & Robel, 1998). The aim of the study is to develop a method for fluorescence labelling. Alexa Fluor 488 dye with DHEAS antibody can binds the DHEAS antibody in the rat brain monitored by Cellvizio Lab System. DHEAS antibody (IgG isotype antibodies) was fluorescently conjugated by an amine-reactive compound, Alexa Fluor 5-SDP ester 488 dye. The resultant Alexa Fluor 488-conjugated antibodies were collected and analyzed by UV-Vis spectrophotometer instrument. The absorbance of the protein-dye conjugate at 280 nm and 494 nm were measured. Then, the degree of labeling (DOL) was calculated to achieve the desired results. Fluorescence labelling were carried out into the CA1 region of hippocampus Sprague-Dawley rat. We reported that the conjugation was successful. Optimal labeling depending on degree of labeling (DOL) needs some necessity to achieve and effective binding to the target neurosteroid, DHEAS. Cellvizio Lab system connected with Fiber Fluorescence Microscopy (FFM) probe is presented as a new approach in real-time imaging of DHEAS. In conclusion, we have developed a new method of DHEAS-Alexa Fluor fluorescence labelling to visualize and evaluate the changes of DHEAS fluorescence level in the rat hippocampus. This novel approach as a diagnostic tool and can be used to better understand the mechanisms and functions of DHEAS and other neurosteroids in future research.